Clementine : the life of Mrs. Winston Churchill - Purnell, Sonia (Viking, 2015)
A portrait of Winston Churchill's extraordinary wife and her lesser-known role in World War II discusses her relationship with political mentor Eleanor Roosevelt, her role in safeguarding Churchill's health throughout key historical events and her controversial family priorities.